Prácticas agronómicas empleadas para prevenir el acame en el cultivo de arroz (Oryza sativa L.) - Solis Vera, Jhon Alexander (2024)
The research analyzed the agronomic practices used to prevent lodging in rice cultivation (Oryza sativa L.). The objectives set were to describe the various factors that cause lodging in plants and to know the various agricultural practices to avoid lodging in rice cultivation. This document was prepared using bibliographic information from various sources, such as websites, articles, scientific articles, magazines and books. The conclusions determined that the factors causing lodging include plants with limited root development (insufficient anchorage), high soil humidity resulting from excess irrigation or flooding due to rain, and wind speeds greater than 30 km/h. The various agricultural practices used to mitigate lodging in rice cultivation involve transitioning to a shorter variety, managing weeds, adjusting or reducing planting density, advancing tillage techniques to minimize damage to plants, increasing soil depth, managing insect pests and transitioning to a variety that responds optimally to applied nitrogen. The farmer plays a crucial role in preventing lodging by implementing appropriate nutritional, agronomic and phytosanitary management practices. These efforts are intended to minimize conditions that favor lodging and ultimately improve the plant's anchor strength, allowing it to withstand strong winds more effectively.